2012
DOI: 10.1128/cvi.00381-12
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Phase IB Clinical Trial of an Alhydrogel-Adsorbed Recombinant Ricin Vaccine

Abstract: There is no FDA-approved vaccine for the potent plant toxin ricin. We have developed a recombinant ricin vaccine, RiVax. Without adjuvant it is safe and immunogenic in mice, rabbits, and humans. Based on our studies in mice, we now report the results of a small clinical trial with Alhydrogel-adsorbed RiVax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 18 publications
(31 reference statements)
1
44
0
Order By: Relevance
“…Although RiVax and RVEc are currently being tested in phase I clinical trials as aluminum-adsorbed vaccines (18)(19)(20)(21)(22), our study is the first to compare the two vaccines sideby-side in an animal model. We compared RiVax and RVEc adsorbed to Alhydrogel and administered to mice s.c. in a 2-or 3-dose immunization regimen across a range of doses (0.3 to 20 g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RiVax and RVEc are currently being tested in phase I clinical trials as aluminum-adsorbed vaccines (18)(19)(20)(21)(22), our study is the first to compare the two vaccines sideby-side in an animal model. We compared RiVax and RVEc adsorbed to Alhydrogel and administered to mice s.c. in a 2-or 3-dose immunization regimen across a range of doses (0.3 to 20 g).…”
Section: Resultsmentioning
confidence: 99%
“…route elicits toxin-specific serum IgG antibodies (Abs) that are sufficient to confer protection against a lethal dose of ricin (8)(9)(10)(15)(16)(17). Phase I clinical trials have demonstrated that RiVax is safe and immunogenic in healthy human volunteers (18,19). Similarly, RVEc is effective at eliciting toxin-neutralizing antibodies in mice and rabbits (20)(21)(22)(23) and is now in phase I clinical trials.…”
mentioning
confidence: 99%
“…Ricin's enzymatic subunit (RTA) is of particular interest to the biodefense research community as two recombinant RTAbased vaccines, RiVax and RVEc, are being evaluated in preclinical and clinical studies (38)(39)(40). Predicting the efficacy of these two vaccine candidates in humans is challenging, because neither the anti-ricin serum IgG titer nor the TNA is necessarily a reliable predictor of protective immunity (41).…”
Section: Discussionmentioning
confidence: 99%
“…RiVax, for example, is a recombinant, attenuated derivative of the enzymatic subunit of ricin toxin (RTA), which has been deemed to be safe for human use (4,5). Unfortunately, phase I clinical trials indicated that even repeated high-dose immunizations were relatively poor at stimulating ricin-specific IgG antibodies and toxin-neutralizing activity (TNA) in sera of volunteers.…”
mentioning
confidence: 99%
“…immunization model. We chose to use RiVax and RVEc for these studies, because they are each well-characterized investigational vaccine antigens that have been deemed safe in phase I clinical trials (4,5). Both are recombinant, nontoxic derivatives of ricin's enzymatic subunit, RTA.…”
mentioning
confidence: 99%